The Great Boer War - Doyle, Arthur Conan, 1859-1930 (Salt Lake City, UT : Project Gutenberg, 2002)
"The Great Boer War" by Arthur Conan Doyle is a non-fiction work published in 1900. Written while the conflict was still unfolding, Doyle chronicles the battles, sieges, and military campaigns between British forces and Boer nations in South Africa. Drawing from conversations with soldiers and Boers alike, he documented major engagements from Talana Hill to the guerilla warfare that followed. The book underwent sixteen editions by war's end in 1902, with Doyle constantly revising his account as events continued to unfold beyond his initial expectations. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Great_Boer_War
Release date is 2002-02-01
Produced by Robert Laing, Sue Asscher, and David Widger
Keywords: South African War, 1899-1902